The Effect of Prompt Length on Student’s Speaking Performance and Use of Target Vocabulary - Akhondi, Masoumeh (2007)
The purpose of this study is to investigate the impact of the length of prompt (written stimulus) on the interviewee’s performance in language proficiency interview. The main quantitative objective is to determine the extent to which the interviewee who receives long/short prompt uses the target vocabulary from the prompt in his speech. Qualitatively, this research was attempted to determine the effectiveness of the long/short prompts on the quality of the student’s overall performance. Here, quality refers to the student’s ability to produce extended, coherent, as well as cohesive chunks of speech. It was hypothesized that, “there is no significant difference in using target vocabulary among the groups receiving long/short and no prompt.” In an experimental randomized subjects posttest-only control group design, 45 participants, comprising the three groups, attended the interviews. The participants received the long (600 words) and the short (300 words) prompts pertaining to the topic prior to the interview, while the control group experienced a prompt-less interview. The following research questions were answered: 1. Will the long prompt group interviewees, receiving heavier target vocabulary load prompts, compared to the short prompt group participants have less difficulty in finding the most appropriate vocabulary to come up with the posed questions? 2. Will the long prompt group perform qualitatively better? After an Analysis of Variance (ANOVA), quantitative findings of the post hoc comparison among the three groups revealed that the difference between the two experimental groups is not statistically significant (p>.05), yet there were differences observed between each of the experimental group and the control group (p<.05). For the qualitative analysis of the data, verbal protocol analysis applied. The findings revealed that, giving interviewee prompt with higher lexical density and higher vocabulary load has noticeably affected his performance. The content of the prompts has provided the fundamental floor for the interviewees to ground his speech on which led to producing more coherent and more cohesive chunks of speech.